Einstein–Yang–Mills-Aether Theory with Nonlinear Axion Field: Decay of Color Aether and the Axionic Dark Matter Production - Balakin, Alexander B.; Kiselev, Gleb B. (Symmetry (Basel), 2022)
We establish a nonlinear version of the SU(N)-symmetric theory, which describes self-consistently the interaction between the gravitational, gauge, vector and pseudoscalar (axion) fields. In the context of this theory the SU(N)-symmetric multiplet of vector fields is associated with the color aether, the decay of which in the early Universe produced the canonic dynamic aether and the axionic dark matter. The SU(N)-symmetric Yang–Mills field, associated with the color aether, forms the source, which transfers the energy of the decaying color aether to the axion field. The nonlinear modification of the model uses explicitly the requirement of discrete symmetry, prescribed by the axion field, and is based on the analogy with a nonlinear physical pendulum. We show that in the framework of this nonlinear regular model, the axion field can grow to an arbitrarily large value, thus explaining the abundance of the axionic dark matter in the Universe.